Pengaruh Relaksasi Benson terhadap Kualitas Tidur Mahasiswa Fakultas Kedokteran Universitas Diponegoro - Roselina, Jessica; Kesoema, Tanti Ajoe; Pasmanasari, Elta Diah; Basyar, Edwin (PERDOSNI, 2022)
Introduction: Sleep is the basic need that should be fulfilled to help the body to work optimally. Sleep disorders are quite prevalent among medical students. Sleep deprived medical students experience decreased cognitive function, mood, alertness, and fatigue. Benson relaxation is a non-pharmacological therapy that can improve sleep quality in elderly. Limited study was published on the effect of Benson relaxation on young adults’ sleep quality. Aim: To analyze the effect of Benson relaxation on sleep quality in students of Faculty of Medicine Diponegoro University. Methods: A non-invasive quasi experimental study with one group pre and post-test design was conducted. Which involved 29 medical students from class of 2018-2021. Purposive sampling technique was performed. Benson relaxation was done for 14 consecutive days, 15 minutes every day. The subject’s sleep quality was assessed by the PSQI questionnaire before and after Benson relaxation treatment. Data was analyzed using IBM SPSS Statistics 22.0 and the test used was paired T-test. Results: The pre-test score mean was 9,38 ± 1,821 meanwhile the post-test score mean was 4,31 ± 2,106. There was statistically significant change in sleep quality before and after Benson relaxation (p = 0,004). Discussion: Benson relaxation increased sleep quality in students of Faculty of Medicine Diponegoro University. Keywords: Sleep quality, medical students, Benson relaxation